The Legal Liability of an Employer for Acts of Sexual Abuse Committed by an Employee: Recent Developments in Australian Law - Williams, Peter (2003)
Sexual abuse has been a much publicised issue in Australia recently, particularly in the context of schools and churches. A very recent decision of the High Court of Australia has considered two grounds upon which an education authority might be held liable for acts of sexual abuse committed by teachers against students: the non-delegable duty of care owed by an education authority and the principle of vicarious liability which governs whether an employer can be liable for the wrongs done by employees. In the judgment, some members of the High Court draw parallels between how the two grounds of liability might apply in the context of sexual abuse by teachers at schools and how they might apply in the context of sexual abuse by employees in institutions such as nursing homes, old people's homes, geriatric wards and daycare centres. The decision therefore raises important questions for those who are involved in the allied health industry.